Pharmacokinetics, Mass Balance, and Biotransformation of [14C]tinengotinib, A Novel Multi-target Kinase Inhibitor, in Healthy Subjects - Shumao Ni; Sheng Ma; Yingying Yu; Zhenwen Yu; Yujia Zhu; Xiaofen Sun; Lin Li; Caixia Sun; Hui Wang; Peng Peng; Zheming Gu; Hua Zhang; et al. (Adis, Springer Healthcare, 2024)
Abstract Background and Objective Tinengotinib, a novel multi-target small molecule kinase inhibitor, is currently undergoing phase II clinical trial in the USA and China. The purpose of this open-label study was to investigate the absorption, metabolism, and excretion of [14C]tinengotinib following a single oral dose in healthy subjects. Methods Six healthy male subjects received a single oral dose of [14C]tinengotinib capsules at 10 mg/100 µCi, and blood, urine, and feces samples were collected. Phenotyping experiments were further conducted to confirm the enzymes involved in its metabolism. Results Tinengotinib was rapidly absorbed in plasma with a time to peak drug concentration (T max) of 1.0-4.0 h post-dose and a long terminal half-life (t ½) of 23.7 h. Blood-to-plasma radioactivity concentration ratios across timepoints ranged from 0.780 to 0.827, which indicated minimal association of radioactivity with blood cells. The mean cumulative excreted radioactivity was 99.57% of the dose, including 92.46% (68.65% as unchanged) in feces and 7.11% (0.28% as unchanged) in urine. In addition to unchanged tinengotinib, a total of 11 radioactive metabolites were identified in plasma, urine, and feces. The most abundant circulating radioactivity was the parent drug in plasma, which comprised 88.23% of the total radioactivity area under the concentration-time curve (AUC). Metabolite M410-3 was a major circulating metabolite, accounting for 5.38% of the parent drug exposure and 4.75% of the total drug-related exposure, respectively. All excreted metabolites accounted for less than 5.10% and 1.82% of the dose in feces and urine, respectively. In addition, no unique metabolites were observed in humans. Tinengotinib was metabolized mainly via CYP3A4. Conclusions Overall, tinengotinib demonstrated a complete mass balance with limited renal excretion, no disproportionate blood metabolism, and slow elimination, primarily through the fecal route. The results of this study provide evidence to support the rational use of tinengotinib as a pharmacotherapeutic agent. Registration ChinadrugTrials.org.cn identifier: CTR20212852.